Pengaruh Motivasi Belajar Terhadap Hasil Belajar Siswa Kelas V pada Mata Pelajaran Fikih di MI Terpadu Raudlatul Ulum Depok - Syarif, Ahmad; Suryana, Agus; Wirda; Sundari, Karmila; Maulida, Anna (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study specifically addresses the problem of suboptimal academic performance in the field of fikih among students. This can be discerned by the absence of motivation and enthusiasm among kids, as well as their passive participation in the learning process. This problem required resolution by the implementation of pertinent research. The aim of this study is to evaluate the learning motivation and academic achievements of fifth-grade students in the fikih subject at MIT Raudlatul Ulum Depok. The study employs a correlative quantitative methodology by utilising a random sample procedure. Based on the research and survey results, the learning motivation of fifth-grade students in the subject of fikih at MIT Raudlatul Ulum Depok is deemed adequate. The motivation to study evaluation score instrument is 87.46, which falls into the good range area. The student learning outcomes in this research exclusively target the cognitive domain, with a specific emphasis on acquiring information and comprehension that are customised to the student's developmental stage. Statistical data analysis can be employed to assess the influence of student learning motivation on the learning outcomes of Class V students in the field of jurisprudence. Based on the results of product moment correlation calculations. The correlation coefficient between learning motivation and student learning results in fikih topics is 0.738, indicating a robust correlation. The score exceeds 0.05, indicating a substantial link between learning desire and student learning outcomes in the field of fikih.